Construções do cotidiano: mulheres convivendo com HIV/Aids - Gonçalves, Camila dos Santos (2010)
Sociocultural factors permeate the history of women before the AIDS epidemic and contributing to the spread of HIV transmission in this segment. Aiming to better understand this phenomenon, we sought to understand how HIV-positive women live their everyday lives after the diagnosis of HIV infection. In addition, check feelings, beliefs and ideas triggered by the revelation of HIV positive diagnosis: to elucidate whether there were changes in their daily life: to identify the health concerns, illness and treatment adherence. This work consisted of an empirical study, exploratory qualitative research design, with the application of semi-structured interviews. Data were analyzed using thematic content analysis and supported by the Theory of Social Representations. Participants were women aged 25-50 years who were diagnosed HIV positive for more than six months, who were in attendance at a public health HIV/AIDS reference in a city in the state of Rio Grande do Sul, Brazil. Data collection occurred during January-August 2010. As a result of this search was built two articles. The first was entitled Women and HIV/AIDS: a clipping of the epidemic feminization', aimed to identify the feelings, beliefs and ideas about the diagnosis received, the sharing of the diagnosis, and the consequences generated by infection of motherhood and marital relationship. The second is called 'Daily life of women with HIV/AIDS: a reading in social representations' which investigated the social representations of women about the infection of HIV / AIDS and its consequences for living with the diagnosis. The conclusions point to the necessary reflection on the vulnerability and expectations of women regarding gender relations. The statements found in this study indicate a greater empowerment of women with HIV, when it comes to coping with the situation after the diagnosis advocating for health care.